Migration and Cross-Border Financial Flows - Kugler, Maurice (The World Bank, 2017)
Migration facilitates the flow of information between countries, thereby reducing informational frictions that potentially hamper cross-country financial flows. Using a gravity model, migration is found to be highly correlated with financial flows from the migrant's host country to her home country. The correlation is strongest where information problems are more acute (e.g., between culturally more distant countries), for asset types that are more informational sensitive, and for the type of migrants that are most able to enhance the flow of information on their home countries, namely, skilled migrants. These differential effects are interpreted as evidence for the role of migration in reducing information frictions between countries